HBO1 promotes cell proliferation in bladder cancer via activation of Wnt/β‐catenin signaling. Issue 1 (2nd September 2017) - Chen, Zhaohui; Zhou, Lijie; Wang, Longwang; Kazobinka, Gallina; Zhang, Xiaoping; Han, Xiaomin; Li, Bin; Hou, Teng
Abstract : Histone acetyltransferase binding to ORC1 (HBO1), a histone acetyltransferase, was recently identified as an oncoprotein; however, its role in bladder cancer remains unknown. In this study, we showed that HBO1 was highly expressed at both the mRNA and the protein levels in bladder cancer. HBO1 expression was associated with the clinical features of human bladder cancer, including tumor size ( P = 0.018) and T ( P = 0.007) classifications. Patients with higher HBO1 expression had shorter recurrence‐free survival time, whereas patients with lower HBO1 expression had better survival time. Moreover, we found that ectopic overexpression of HBO1 promoted, whereas HBO1 silencing inhibited tumor growth in bladder cancer cells both in vitro and in vivo. We further demonstrated that upregulation of HBO1 activated the Wnt/β‐catenin signaling pathway and led to nuclear localization of β‐catenin and upregulation of downstream targets of of Wnt/β‐catenin signaling. These findings suggest that HBO1 plays a key role in the progression of bladder cancer via the Wnt/β‐catenin pathway, and may serve as a potential therapeutic target for the treatment of bladder cancer.